(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The aim of this study was to identify the role of the Palestinian government administration in reducing obstacles on facing the housing problem in the Gaza Strip, using the questionnaire as a tool for study which targeted the employees at higher levels in the relevant ministries، and municipalities، there number was (123) in charge. It has been distributed on the entire study population، and recovered (112) questionnaire accounted for (91). The study used descriptive analytical method. The study found that the government’s direct efforts have little impact on facing the housing problem in the Gaza Strip, while its management of partner sector efforts (the private sector and non-governmental organizations) has a moderate impact, and the government largely believes in the role of these sectors in facing the problem. The study recommended adopting the method of vertical expansion and public housing, designing a new model that integrates the cooperative housing and public housing programs, and the need to develop the level and mechanisms of partnership and coordination between ministries concerned with housing and municipalities. And then with the partner sectors and open permanent channels of communication to discuss policies that encourage these sectors to take initiative and assume responsibilities.